The significance of the Cancún Ministerial: its context, reasons for breakdown and implications for the future - Brink, R G (Department of Public Law, 2023)
This thesis endeavours to examine the context within which the Fifth WTO Ministerial, held between 10 and 14 September 2003 at Cancún, took place and attempts to place in a balanced manner the various reasons for its progressive breakdown and consequent failure. It also looks at the implications for the future of the Multilateral Trading Negotiations system and its alternatives being the growing of protectionist policies and the possibility of the further growth of bilateral agreements. In order to place the agreements into context, the paper first considers the state of Free Trade Agreements prior to the formation of the World Trade Organisation (WTO) followed by those agreements entered into under the auspices of the WTO but before the Cancún Ministerial. It then surveys the geopolitical and economic context just prior to these talks. A short survey of the priority issues for the developing and developed world follows and then an in-depth discussion of the various factors which may have contributed to the failure of talks at Cancún.